Use of flowcytometric immunophenotyping in the diagnosis and prognosis of acute leukaemias in Sarawak - Voon, Ah Kim (Universiti Malaysia Sarawak, (UNIMAS), 2004)
Acute leukaemia can be classified based on the findings of the morphology, cytochemistry studies, immunophenotyping and cytogenetic studies of the malignant cells. This study involved all new cases of acute leukaemia cases diagnosed at Sarawak General Hospital, Kuching between the period from November 2000 to October 2002. The analysis included morphologic, chytochemistry and immunophenotypic analysis of bone marrow aspirate and peripheral blood.